PENGARUH WAKTU CELUP HOT DIP GALVANIZE PADA BAJA KARBON ASTM A516 GRADE 70 TERHADAP KETAHANAN LAJU KOROSI MENGGUNAKAN METODE WEIGHT LOSS VARIASI PH AIR - Cahaya, Tubagus Hidayatullah; Kardiman, Kardiman; Gusniar, Iwan Nugraha (Gorontalo Journal of Infrastructure and Science Engineering, 2024)
The industrial sector plays a crucial role in the global economy, with energy industries, especially oil and gas, experiencing rapid growth. However, pipeline leaks due to corrosive processes pose significant challenges in this sector. Corrosion, a material degradation process occurring upon contact with the environment, requires prevention and control measures to reduce detrimental effects. Various corrosion prevention methods for steel have been developed, including galvanizing processes such as zinc-rich paint, zinc electroplating, and hot-dip galvanizing, commonly used for comprehensive protection by forming a zinc barrier on steel surfaces. Steel, a widely used construction material, especially low-carbon steel, dominates applications like vehicle manufacturing, railways, and the construction of structures such as pipes, tanks, and ships. Low-carbon steel, with less than 0.3% carbon, exhibits high toughness and malleability but is susceptible to corrosion in corrosive environments. This study focuses on the corrosion resistance of hot-dip galvanized coatings on ASTM A516 Gr 70 carbon steel in a marine environment. The research aims to evaluate the galvanization performance in preventing corrosion and extending the steel's lifespan, particularly in the context of its use as a protective coating for oil and gas pipelines. Corrosion tests using the weight loss method will assess the quality and corrosion resistance of galvanized ASTM A516 Gr 70 carbon steel. The study, underscores the importance of corrosion science in understanding and addressing corrosion challenges in industrial applications. The research is expected to provide insights into corrosion rates under specific conditions and variations in test specimens